Clinical and cytological evaluation of Malassezia pachydermatis in ears of dogs - Campos, Diefrey Ribeiro (2014)
ABSTRACT. Campos D.R., Guberman U.C., Suhett W.G. & Aptekmann K.P. [Clinical and cytological evaluation of Malassezia pachydermatis in ears of dogs.] Caracterização clínica e citológica de Malassezia Pachydermatis da orelha de cães. Revista Brasileira de Medicina Veterinária, 36(2):344-346, 2014. Departamento de Medicina Veterinária, Universidade Federal do Espírito Santo, Alto Universitário, s/nº, Cx Postal 16, Guararema, Alegre, ES 29500-000, Brasil. E- -mail: kapreising@yahoo.com.br Otitis externa has a multifactorial etiology, which may be caused by bacteria, fungi and/or mites. Fungal otitis may be secondary to other agents, mixed (when there is an association of fungi and bacteria) and, more rarely, primary. The main fungal agents are Candida spp. and Malassezia pachydermatis. The most common clinical signs are head shaking, local pain, pinna lesions, otological pruritus and cerumen accumulation. Infection with M. pachydermatis has a dark brown, moist and malodorour cerumen. The objective of this study was to correlate the presence of M. pachydermatis in exudate cytology with clinical manifestations observed in dogs. Cerumen was collected from 86 dogs in a hospital population, independent of age, breed or sex. It was filled up a form containing information about animal identification, clinical signs and otology therapy. Slides were prepared for microscopic examination of cerumen, stained by quick Dift Quick®. It was counted the number of M. pachydermatis by field. A correlation between the presence of cerumen and pruritus was verified. No correlation between the amount of M. pachydermatis observed in cerumen examination and the presence of ear exudate and itching was found in dogs.